1997
DOI: 10.1111/j.1469-7998.1997.tb02799.x
|View full text |Cite
|
Sign up to set email alerts
|

Tail autotomy and extinction in Mediterranean lizards. A preliminary study of continental and insular populations

Abstract: Tail autotomy is one of the main anti‐predator mechanisms of lacertid lizards, but it has been predicted that it is only retained in its full capacity when its benefits exceed its costs (Arnold, 1988). To test this hypothesis, ease of tail shedding was examined in a number of continental and insular lacertid lizard populations, each of which showed a different shedding capacity. Tails are shed more easily in those continental and insular populations where there is a greater probability of predation. In insular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
2
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 26 publications
(24 reference statements)
3
72
2
3
Order By: Relevance
“…Specifically, average durations of tail movement for all taxa analyzed here are substantially longer than analogous times in Eumeces fasciatus (0.8 min), Eumeces laticeps (0.95 min), and Holbrookia garnotii (1.7 min; Vitt and Cooper 1986;Lochetto 1998) and closer but still exceeding those of Hemidactylus mabouia (5.2 min; Meyer et al 2002) and Scincella lateralis (approximately 5 min; Dial and Fitzpatrick 1983). Moreover, the six lacertid species examined here appear to have average times of tail movement considerably longer than analogous times given in the only other study on lacertid lizard autotomy published to date (Perez-Mellado et al 1997). These differences stem most likely from small sample sizes in previous studies, as well as differences in methodology (e.g., differences in criteria in when tail movement was considered to have ceased).…”
Section: Discussionmentioning
confidence: 43%
See 4 more Smart Citations
“…Specifically, average durations of tail movement for all taxa analyzed here are substantially longer than analogous times in Eumeces fasciatus (0.8 min), Eumeces laticeps (0.95 min), and Holbrookia garnotii (1.7 min; Vitt and Cooper 1986;Lochetto 1998) and closer but still exceeding those of Hemidactylus mabouia (5.2 min; Meyer et al 2002) and Scincella lateralis (approximately 5 min; Dial and Fitzpatrick 1983). Moreover, the six lacertid species examined here appear to have average times of tail movement considerably longer than analogous times given in the only other study on lacertid lizard autotomy published to date (Perez-Mellado et al 1997). These differences stem most likely from small sample sizes in previous studies, as well as differences in methodology (e.g., differences in criteria in when tail movement was considered to have ceased).…”
Section: Discussionmentioning
confidence: 43%
“…Tail autotomy is considered an important antipredator mechanism in lacertid lizards (Arnold 1984;Perez-Mellado et al 1997). Dial and Fitzpatrick (1984) first suggested that the high anaerobic capacity of autotomized lizard tails is an adaptation to predation because it allows for prolonged tail thrashing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations